2014
DOI: 10.5152/npa.2014.7213
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Serum S100B Levels with Infarction Size and Clinical Outcome in Acute Ischemic Stroke Patients

Abstract: The detection of high S100B levels in peripheral circulation after acute ischemic stroke and the correlations of S100B levels with infarct size (good) and disability (poor) imply that S100B protein may be used as a peripheral marker in acute ischemic stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…Furthermore, serum levels of the astrocyte calcium-binding protein, S100B, also did not differ statistically between the AIS + D and AIS groups, although a trend towards higher levels in the AIS + D group was seen at p = 0.065. Serum S100B is also elevated after acute ischemic stroke, showing a positive correlation to infarct size [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serum levels of the astrocyte calcium-binding protein, S100B, also did not differ statistically between the AIS + D and AIS groups, although a trend towards higher levels in the AIS + D group was seen at p = 0.065. Serum S100B is also elevated after acute ischemic stroke, showing a positive correlation to infarct size [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, the exact aetiology and pathogenetic mechanisms of IS remain unclear. Recently, increasing evidence has indicated that serum S100B levels may be used as a novel biomarker for IS 33 35 . Nevertheless, the mechanisms leading to elevated serum S100B are unknown, but this is believed to lead to aggravation of the development of IS.…”
Section: Discussionmentioning
confidence: 99%
“… 47 reported that serum-S100B was positively correlated with plasma high-sensitivity C-reactive protein. In addition, clinical and experimental studies have demonstrated that the levels of serum S100B were elevated in patients with IS 33 , 34 , 48 . Furthermore, a previous study found that knockdown of S100B in atherosclerotic mice can improve the brain’s recovery function and reduced infarctions 49 .…”
Section: Discussionmentioning
confidence: 99%
“…S100β is among the family of non-ubiquitous Ca 2+ -modulated proteins and it is mainly produced by astrocytes. It plays an important role in nerve growth, differentiation, and reparation of nerves [42,43,44]. It is a glial protein, with a molecular weight of approximately 10 kDa, located intracellularly [45] and found in abundance in the cerebral astroglial compartment, peripheral Schwann cells, and extraneuronally in melanocytes, adipocytes, and chondrocytes [46].…”
Section: Introductionmentioning
confidence: 99%